Managing product variety in international supply chains - Er, Mahendrawathi (2004)
In today's business environment, firms increasingly think in the context of a supply chain rather than a single factory and operate globally rather than in a single nation. At the same time, we have also witnessed increasing breadth in product ranges and accelerating rates of new product introduction in the marketplace. While there are potentially strong interrelationships between product variety and international supply chain management, the issues have been addressed separately in the research literature. Owing to this shortfall, this study investigates the issue of product variety in the context of international supply networks. More specifically, the study seeks to gain insights on different types of co-ordination and configuration of international supply network and to more deeply understand the impact of, and the interrelationships between, product variety, supply lead-time and demand uncertainty on the performance of an international supply chain. Empirical and simulation studies have been conducted to fulfil the above objectives.